Tapir population patterns under the disappearance of free-standing water - Reyna-Hurtado, Rafael; Sima-Pantí, David; Andrade, Maria; Padilla, Angelica; Retana-Guaiscon, Oscar; Sanchez-Pinzón, Khiavett (THERYA, 2019)
Baird’s tapir is the largest Neotropical tapir species, and it is considered Endangered by the IUCN. The Calakmul Biosphere Reserve (CBR) is the largest protected tropical forest in Mexico. The CBR is at the heart of the Maya Forest, a tri-national forest located in Mexico, Guatemala, and Belize that is the largest tropical forest outside the Amazon River basin. Free-standing water in the CBR occurs in only a few ephemeral ponds. These ponds are rare in the landscape, with a mean density of one pond in every 10 km2, and with an average distance among ponds of 3 km. Only some of these ponds have free-standing water in every year. A decreasing trend in water availability from these ponds was detected from 2008 to 2018. Our present objective was to document population of the tapirs during these 11 years, and reveal any relationship to the pattern of water availability. Using the technique of photo-trapping, we monitored from 9 to 15 ponds over a period of 8 years (a total of more than 18,000 camera-days) during the 11-year period. Results showed that although the population remained relatively stable, the index of relative abundance indicated a slight decrease in population abundance and in some sites seemed at least superficially associated with decreasing water availability. Such long-term population studies are becoming more important for estimating the impacts of possible changes and for predicting the future of populations. In turn, they assist the conservation of endangered and sensitive species such as Baird’s tapir.